Reattachment of the greater trochanter in total hip arthroplasty: the pin-sleeve system compared with the Dall-Miles cable grip system - Takahira, Naonobu (Springer-Verlag, 2010)
The purpose of this study was to compare two different types of fixation systems used to reattach the greater trochanter after revision or total hip arthroplasty. This is a retrospective review of the results of patients that were treated with the two systems. We reviewed the clinical and radiological records of 35 hips with the Dall-Miles cable grip system (DMCGS) and 42 hips with the pin-sleeve system (PSS); follow-up averaged 24 months (range, 4–54) and 30 months (range, 11–42), respectively. The incidences of unsatisfactory clinical and radiological results in the PSS group was less than half that in the DMCGS group. Significant differences were found between the groups with respect to discomfort, tenderness, pain on motion, cable fragmentation, and bone absorption. Compared with the DMCGS, these results suggest the PSS could be the instrument of choice for re-attachment of the greater trochanter in hip arthroplasty.